(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article addresses the critical challenge of forming and implementing a strategic management model in vocational education institutions of Uzbekistan, where traditional administrative approaches have proven insufficient for meeting the rapidly evolving demands of the modern labor market. The study critically analyzes the theoretical foundations of strategic management in education, drawing upon Total Quality Management (TQM), the PDCA cycle, and internationally recognized quality assurance frameworks including EQAVET and ISO 21001. The author proposes a structural-functional model comprising institutional-strategic, organizational-structural, and monitoring-evaluative blocks, validated through a quasi-experimental study involving 232 students and 170 administrative leaders across three polytechnics. Results demonstrate a 13.29% increase in education quality indicators in experimental groups and a 15.6% improvement in strategic management competencies among institutional leaders. The article concludes with recommendations for systemic adoption of evidence-based strategic management in vocational education.